Penciptaan karya teater monolog wayang upih moved motion: moved motion - Adi Pranajaya, I Made; Widnyana, I Kadek; Wicaksana, I Dewa Ketut; Akbar, Hanolda Gema (Pusat Penerbitan LP2MPP ISI Bali, 2025)
This artistic research explores the creation of a contemporary monologue puppet theater entitled Moved Motion, inspired by the traditional Wayang Upih made from betel sheath (upih). The work departs from the urgency of revitalizing nearly forgotten local traditions while addressing ecological and philosophical values through artistic innovation. The aim is to transform Wayang Upih into a three-dimensional puppet theater that embodies symbolic narratives of karma, transformation, and human existential reflection. The study employs a practice-led research approach, integrated with the Balinese creation framework Asta Widhi Kawya, which guides the process from conceptualization, narrative development, rehearsal, to final performance. Data were obtained through literature review, field observation, and direct experimentation in collaboration with a local art community. The result is a performance that combines traditional material with contemporary dramaturgy, featuring symbolic figures such as the human puppet, butterfly, and mirror to represent bondage, hope, and self-reflection. The novelty of this work lies in the ecological use of natural materials, the integration of personal narrative with traditional philosophy, and the re-positioning of Wayang Upih within contemporary performing arts. This creation contributes to the preservation and reinterpretation of Balinese puppetry while offering a sustainable model for innovative artistic practices.